Berita Hoax dalam Perspektif Islam - Erwan Efendi; Farah dalilah balqis; Ariati Putri Siagian; M. Fauzi Sirait (Journal on Education, 2023)
The purpose of this writing is to find out what news is included in the fake news grouping and how Islam views this, whether there are severe sanctions against the perpetrators of spreading the fake news so as to raise awareness from individuals not to carry out these activities. This research method uses a qualitative descriptive research method by collecting data through literature obtained through the Google Scholar search page and describing the data collected related to hoax news from an Islamic perspective. Islam displays that spreading hoax news will divide relations so that it is strictly prohibited. By conducting this research it is known that Islam does not justify the act of spreading fake news.